Wobble ([Canberra, A.C.T.] : Wobble, 2010)
"Wobble is a collective put together to cook up new gallery space, curate, host events and sell artwork. In collaboration with some of Canberra's favorite bars and cafés, ... we bring you a series of parties and a collection of Canberra's best art and design."
Title from title page (viewed on 16 Aug. 2011)
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://wobble.cc
Selected for archiving
Keywords: Art and design -- Australian Capital Territory -- Canberra; Art -- Australian Capital Territory -- Canberra